Design, synthesis and anti-Alzheimer's disease activity study of xanthone derivatives based on multi-target strategy. Issue 4 (15th February 2020) - Kou, Xiaodi; Song, Lulu; Wang, Yunhua; Yu, Qiao; Ju, Hui; Yang, Aihong; Shen, Rui
Graphical abstract: Abstract: A series of xanthone derivatives were designed, synthesized and evaluated as multifunctional ligands against Alzheimer's disease (AD). In vitro studies showed all xanthone derivatives had good metal chelating property and exhibited selective inhibitory activity against Acetylcholinesterase (AChE). In particular, compound 2a showed the highest inhibitory activity against AChE, and the IC50 value was (0.328 ± 0.001) μM, which was comparable to tacrine. Kinetic analysis and molecular docking studies indicated that these derivatives targeted both the catalytically active site (CAS) and the peripheral anion site (PAS) of AChE. Moreover, all derivatives showed higher anti-oxidative activity than vitamin C. Furthermore, copper complex had higher anti-AChE activity and antioxidant activity. Thus, these xanthone derivatives are potential multi-targeted-directed ligands for further development for the treatment of AD.